Adequacy assessment of generating systems incorporating storage integrated virtual power plants - Bagchi, Arijit (2020)
This paper investigates the impacts of incorporating energy storage devices (ESD) into a virtual power plant (VPP) model and subsequently using it for performing generating system adequacy studies. A two-step linearized optimization formulation is proposed for developing the overall VPP model featuring the aggregated characteristics and capacities of several distributed generators (DG), ESDs and loads together with distribution network information like topology and constraints. While the first step determines the (charging or discharging) operating mode of the batteries, the second step outputs the optimal dispatch schedules for the DGs and ESDs in accordance with a fair energy allocation based operating strategy adopted in this paper. The VPP is modeled using an augmented IEEE 69-bus distribution network, and the overall generation adequacy studies incorporating the VPP are carried out on the IEEE Reliability Test System using a sequential simulation algorithm. Several indices are presented for quantifying the impacts of the ESDs' incorporation on the VPP model's performance. Finally, sensitivity studies conducted for investigating the effects of variations in the ESD rated capacities and charging/discharging periods on the VPP performance and system adequacy indices are also described.